Resveratrol‐mediated apoptosis of hodgkin lymphoma cells involves SIRT1 inhibition and FOXO3a hyperacetylation. Issue 5 (7th August 2012) - Frazzi, Raffaele; Valli, Riccardo; Tamagnini, Ione; Casali, Bruno; Latruffe, Norbert; Merli, Francesco
Abstract Resveratrol (RSV), a plant‐derived stilbene, induces cell death in Hodgkin lymphoma (HL)‐derived L‐428 cells in a dose‐dependent manner (IC50 = 27 μM, trypan blue exclusion assay). At a lower range (25 μM), RSV treatment for 48 hr causes arrest in the S‐phase of the cell cycle, while at a higher concentration range (50 μM), apoptosis can be detected, with activation of caspase‐3. The histone/protein deacetylase SIRT1 has been described as a putative target of RSV action in other model systems, even though its role in cancer cells is still controversial. Here we show that RSV, at both concentration ranges, leads to a marked increase in p53, while a decrease of SIRT1 expression level, as well as enzyme activity, only occurred at the higher concentration range. Concomitantly, however, treatments at both concentration ranges resulted in a marked increase in K373‐acetylated p53 and lysine‐acetylated FOXO3a. Immunohistochemical stainings of human lymph nodes show a preferential distribution of SIRT1 in the germinal center of the follicles while the mantle zone shows nearly no staining to few positive cells. The classical HL‐affected lymph nodes show a strong positivity of the diagnostic Hodgkin Reed‐Sternberg cells. Notably, both the HL‐derived cell lines and the Hodgkin Reed‐Sternberg cells of the affected lymph nodes derive from germinal center‐derived B cells. The study of SIRT1 distribution and expression on a larger number of biopsies might disclose a novel role for this histone/protein deacetylase as therapeutic target.